Optimalisasi Throughput LTE Femtocell Pada Jaringan Koeksistensi LTE-GSM - Yaser, Muhammad (Website, 2023)
Throughput on the GSM and LTE Femto coexistence network is highly dependent on the distribution conditions of the femtocells, including the number and position of the femtocells. In previous studies, there has been much discussion about network interference management for LTE femtocell integrated with GSM macrocells. However, previous studies have not clearly discussed the strategy for optimizing the throughput value in this coexistence network. LTE femtocell throughput performance is analyzed mathematically. The simulation results show that when femtocells are deployed near GSM BSs, namely at a distance of x = 0.1R, accommodating one and more LTE femtocells on each GSM macrocell causes a decrease in throughput of around 6.3 kbits/s and LTE femtocell throughput continues to decrease due to the increasing number of femtocells deployed on GSM macrocell. Meanwhile, the throughput of LTE femtocell increases as the distance between the femtocell and the GSM BS increases. When changing from the distance x = 0.1R to x = R, the LTE femtocell throughput increases by about 1.3x102 kbits/s. So Optimization of LTE femtocell throughput can be done by reducing the number of femtocells deployed on GSM macrocells and adjusting LTE femtocell distribution patterns away from GSM BS. Keywords— Throughput; LTE femtocell; GSM macrocell; coexistence